Sorption of tebuconazole onto selected soil minerals and humic acids - Cadková, Eva; Komárek, Michael; Kaliszová, Regina; Koudelková, Věra; Dvořák, Jiří; Vaněk, Aleš (Journal of environmental science and health. Part B, Pesticides, food contaminants, and agricultural wastes, 2012)
The aim of the present study was to investigate tebuconazole sorption on common soil minerals (birnessite, ferrihydrite, goethite, calcite and illite) and humic acids (representing soil organic matter). Tebuconazole was used (i) in the commercial form Horizon 250 EW and (ii) as an analytical grade pure chemical. In the experiment with the commercially available tebuconazole, a significant pH-dependent sorption onto the oxides was observed (decreasing sorption with increasing pH). The highest sorption was found for ferrihydrite due to its high specific surface area, followed by humic acids, birnessite, goethite and illite. No detectable sorption was found for calcite. The sorption of analytical grade tebuconazole on all selected minerals was significantly lower compared to the commercial product. The sorption was the highest for humic acids, followed by ferrihydrite and illite and almost negligible for goethite and birnessite without any pH dependence. Again, no sorption was observed for calcite. The differences in sorption of the commercially available and analytical grade tebuconazole can be attributed to the additives (e.g., solvents) present in the commercial product. This work proved the importance of soil mineralogy and composition of the commercially available pesticides on the behavior of tebuconazole in soils.
Keywords: pesticidy; Adsorption; látky znečišťující půdu; Soil Pollutants; adsorpce; Soil; půda; Minerals; Triazoles; Humic Substances; triazoly; huminové látky; Pesticides; minerály